Counter electrode electrocatalysts from binary Pd–Co alloy nanoparticles for dye-sensitized solar cells. (February 2016) - He, Benlin; Tang, Qunwei; Zhang, Huihui; Yu, Liangmin
Highlights: Pd–Co alloy catalysts are fabricated by a facile rapid chemical reduction method. The charge-transfer ability toward iodide reduction is significantly enhanced. A conversion efficiency of 6.44% is obtained in its DSSC. The strategy provides new opportunities for efficient but low-cost DSSCs. Abstract: A class of alloyed Pd–Co catalysts are prepared by a mild solution method and subsequently blended with poly(vinylidene fluoride) (PVDF) binder for coating cost-effective counter electrodes (CEs) of dye-sensitized solar cells (DSSCs). The electrocatalytic activity for the I − /I3 − redox electrolyte as well as photovoltaic performances of DSSCs are optimized by adjusting stoichiometric Pd/Co ratios. Due to the merits of resultant Pd–Co alloy CEs on good electrical conduction, rapid charge-transfer ability, and increased electrocatalytic activity, a maximum conversion efficiency of 6.44% is determined on the optimized DSSCs in comparable to 6.18% for Pt CE based DSSC. It is obvious that Pd–Co alloy CEs can be a better cost-effective and efficient alternative due to the expensive price and scarcity of Pt for the large scale applications of DSSCs.